Diet of the small-spotted catshark Scyliorhinus canicula in the Aegean Sea (eastern Mediterranean). Issue 2 (7th February 2017) - Kousteni, Vasiliki; Karachle, Paraskevi K.; Megalofonou, Persefoni
ABSTRACT: The diet of the small-spotted catshark Scyliorhinus canicula, captured in the Aegean Sea by bottom-trawl from 2006 to 2012, was investigated with respect to sex, maturity condition, sampling location and season. The stomach contents of 432 specimens, measuring from 144 to 517 mm in total length, were analysed. The cumulative prey curve showed that the sample size was adequate to describe the species' diet, which was quantified using the percentage gravimetric composition ( %W ). The identified prey items belonged to eight major groups: Teleostei, Chondrichthyes, Crustacea, Cephalopoda, Annelida, Echinodermata, phanerogams and macroalgae, with Teleostei, Crustacea and Cephalopoda being the most consumed in both females ( %W = 48.1, 16.0 and 31.4, respectively) and males ( %W = 33.9, 31.6 and 29.8, respectively). Higher diet diversity was observed in males than females, in immature individuals than mature ones, regardless of sex, as well as in spring in comparison to autumn and winter. Feeding intensity seemed to be influenced mainly by sex and maturity condition. No significant dietary overlap was observed for all possible combinations of the factors examined. Gut indices were compared between the two sexes with females showing statistically significantly higher median relative gut length, as well as a longer gut than males of the same length. Based on the diet composition, S. canicula can be considered a generalist predator consuming, with geographical differentiation, a wide variety of benthic taxa. The estimated fractional trophic level ( τ = 4.22) classified the species as a carnivore with a preference for Teleostei and Cephalopoda, thus confirming its key role in the food web.